Comparison of carbon dioxide control during pressure controlled versus pressure-regulated volume controlled ventilation in children (CoCO2): protocol for a pilot digital randomised controlled trial in a quaternary paediatric intensive care unit - Luregn J Schlapbach; Barbara Brotschi; Kristen S Gibbons; Florian Zapf; Rebeca Mozun; Daphné Chopard; Philipp Baumann; Anika Adam; Vera Jaeggi; Beat Bangerter; Juerg Burren (BMJ Open)
Introduction Digital trials are a promising strategy to increase the evidence base for common interventions and may convey considerable efficiency benefits in trial conduct. Although paediatric intensive care units (PICUs) are rich in routine electronic data, highly pragmatic digital trials in this field remain scarce. There are unmet evidence needs for optimal mechanical ventilation modes in paediatric intensive care. We aim to test the feasibility of a digital PICU trial comparing two modes of invasive mechanical ventilation using carbon dioxide (CO2) control as the outcome measure.Methods and analysis Single-centre, open-labelled, randomised controlled pilot trial with two parallel treatment arms comparing pressure control versus pressure-regulated volume control. Patients are eligible if aged <18 years, weighing >2 kg, have an arterial line and require >60 min of mechanical ventilation during PICU hospitalisation at the University Children’s Hospital Zurich. Exclusion criteria include cardiac shunt lesions, pulmonary hypertension under treatment and intracranial hypertension. CO2 is measured using three methods: end-tidal (continuous), transcutaneous (continuous) and blood gas analyses (intermittent). Baseline, intervention and outcome data are collected electronically from the patients’ routine electronic health records. The primary feasibility outcome is adherence to the assigned ventilation mode, while the primary physiological outcome is the proportion of time spent within the target range of CO2 (end-tidal, normocarbia defined as CO2 ≥ 4.5 and ≤ 6 kPa). Both primary outcomes are captured digitally every minute from randomisation until censoring (at 48 hours after randomisation, extubation, discharge or death, whichever comes first). Analysis will occur on an intention-to-treat basis. We aim to enrol 60 patients in total. Recruitment started in January 2024 and continued for 9 months.Ethics and dissemination This study received ethical approval from the Cantonal Ethics Commission of Zurich (identification number: 2022–00829). Study results will be disseminated through publication in a peer-reviewed journal and other media like podcasts.Trial registration number NCT05843123.